Fingerprints of electronic, spin and structural dynamics from resonant inelastic soft X-ray scattering in transient photo-chemical species. Issue 10 (27th February 2018) - Norell, Jesper; Jay, Raphael M.; Hantschmann, Markus; Eckert, Sebastian; Guo, Meiyuan; Gaffney, Kelly J.; Wernet, Philippe; Lundberg, Marcus; Föhlisch, Alexander; Odelius, Michael
Abstract : Inversion-symmetry separation of electronic state manifolds in RIXS enables identification of transient species in photo-chemical dynamics. Abstract : We describe how inversion symmetry separation of electronic state manifolds in resonant inelastic soft X-ray scattering (RIXS) can be applied to probe excited-state dynamics with compelling selectivity. In a case study of Fe L3 -edge RIXS in the ferricyanide complex Fe(CN)6 3−, we demonstrate with multi-configurational restricted active space spectrum simulations how the information content of RIXS spectral fingerprints can be used to unambiguously separate species of different electronic configurations, spin multiplicities, and structures, with possible involvement in the decay dynamics of photo-excited ligand-to-metal charge-transfer. Specifically, we propose that this could be applied to confirm or reject the presence of a hitherto elusive transient Quartet species. Thus, RIXS offers a particular possibility to settle a recent controversy regarding the decay pathway, and we expect the technique to be similarly applicable in other model systems of photo-induced dynamics.